Impact of Oncoming Headlight Glare With Cataracts: A Pilot Study - Hwang, Alex D.; Tuccar-Burak, Merve; Goldstein, Robert; Peli, Eli (Frontiers in Psychology, 2018)
Purpose: Oncoming headlight glare (HLG) reduces the visibility of objects on the road and may affect the safety of nighttime driving. With cataracts, the impact of oncoming HLG is expected to be more severe. We used our custom HLG simulator in a driving simulator to measure the impact of HLG on pedestrian detection by normal vision subjects with simulated mild cataracts and by patients with real cataracts. Methods: Five normal vision subjects drove nighttime scenarios under two HLG conditions (with and without HLG: HLGY and HLGN, respectively), and three vision conditions (with plano lens, simulated mild cataract, and optically blurred clip-on). Mild cataract was simulated by applying a 0.8 Bangerter diffusion foil to clip-on plano lenses. The visual acuity with the optically blurred lenses was individually chosen to match the visual acuity with the simulated cataract clip-ons under HLGN. Each nighttime driving scenario contains 24 pedestrian encounters, encompassing four pedestrian types; walking along the left side of the road, walking along the right side of the road, crossing the road from left to right, and crossing the road from right to left. Pedestrian detection performances of five patients with mild real cataracts were measured using the same setup. The cataract patients were tested only in HLGY and HLGN conditions. Participants’ visual acuity and contrast sensitivity were also measured in the simulator with and without stationary HLG. Results: For normal vision subjects, both the presence of oncoming HLG and wearing the simulated cataract clip-on reduced pedestrian detection performance. The subjects performed worst in events where the pedestrian crossed from the left, followed by events where the pedestrian crossed from the right. Significant interactions between HLG condition and other factors were also found: (1) the impact of oncoming HLG with the simulated cataract clip-on was larger than with the plano lens clip-on, (2) the impact of oncoming HLG was larger with the optically blurred clip-on than with the plano lens clip-on, but smaller than with the simulated cataract clip-on, and (3) the impact was larger for the pedestrians that crossed from the left than those that crossed from the right, and for the pedestrians walking along the left side of the road than walking along the right side of the road, suggesting that the pedestrian proximity to the glare source contributed to the performance reduction. Under HLGN, almost no pedestrians were missed with the plano lens or the simulated cataract clip-on (0 and 0.5%, respectively), but under HLGY, the rate of pedestrian misses increased to 0.5 and 6%, respectively. With the optically blurred clip-on, the percent of missed pedestrians under HLGN and HLGY did not change much (5% and 6%, respectively). Untimely response rate increased under HLGY with the plano lens and simulated cataract clip-ons, but the increase with the simulated cataract clip-on was significantly larger than with the plano lens clip-on. The contrast sensitivity with the simulated cataract clip-on was significantly degraded under HLGY. The visual acuity with the plano lens clip-on was significantly improved under HLGY, possibly due to pupil myosis. The impact of HLG measured for real cataract patients was similar to the impact on performance of normal vision subjects with simulated cataract clip-ons. Conclusion: Even with mild (simulated or real) cataracts, a substantial negative effect of oncoming HLG was measurable in the detection of crossing and walking-along pedestrians. The lowered pedestrian detection rates and longer response times with HLGY demonstrate a possible risk that oncoming HLG poses to patients driving with cataracts.